so sánh a=2016^2016+1/2016^2017+1 và b=2016^2015+1/2016^2016+1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Vì 20162016 + 1 < 20162017 + 1
\(\Rightarrow B< \frac{2016^{2016}+1+2015}{2016^{2017}+1+2015}=\frac{2016^{2016}+2016}{2016^{2017}+2016}=\frac{2016\left(2016^{2015}+1\right)}{2016\left(2016^{2016}+1\right)}=\frac{2016^{2015}+1}{2016^{2016}+1}=A\)
Vậy A > B
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
TA có :\(\frac{2015.2016-1}{2015.2016}=\frac{2015.2016}{2015.2016}-\frac{1}{2015.2016}=1-\frac{1}{2015.2016}\)
Ta có:\(\frac{2016.2017-1}{2016.2017}=\frac{2016.2017}{2016.2017}-\frac{1}{2016.2017}=1-\frac{1}{2016.2017}\)
Vì \(2015.2016< 2016.2017\)
\(\Rightarrow\frac{1}{2015.2016}>\frac{1}{2016.2017}\)
\(\Rightarrow1-\frac{1}{2015.2016}< 1-\frac{1}{2016.2017}\)
\(\Rightarrow\frac{2015.2016-1}{2015.2016}< \frac{2016.2017-1}{2016.2017}\)
Vậy \(\frac{2015.2016-1}{2015.2016}< \frac{2016.2017-1}{2016.2017}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\frac{2016}{2017}< 1;\frac{2015}{2016}< 1\)
b)\(\frac{2017}{2016}>1;\frac{2016}{2015}>1\)
=> \(\frac{2016}{2017}\)và
\(\frac{2016}{2017}< 1;\frac{2016}{2015}< 1\)
\(\frac{2017}{2016}>1;\frac{2016}{2015}>1\)
=> \(\frac{2016}{2017}\)và \(\frac{2015}{2016}\)< \(\frac{2017}{2016}\)và \(\frac{2016}{2015}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Vì \(2016^{2016}+1< 2016^{2017}+1\) nên \(\frac{2016^{2016}+1}{2016^{2017}+1}< 1\)
\(\Rightarrow A=\frac{2016^{2016}+1}{2016^{2017}+1}< \frac{2016^{2016}+1+2015}{2016^{2017}+1+2015}=\frac{2016^{2016}+2016}{2016^{2017}+2016}=\frac{2016\left(2016^{2015}+1\right)}{2016\left(2016^{2016}+1\right)}=\frac{2016^{2015}+1}{2016^{2016}+1}=B\)Vậy A < B
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
- \(A=\frac{2015}{2016}+\frac{2016}{2017}>1;\)
- \(B=\frac{2015+2016}{2016+2017}< 1\)
- Nên A>B
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{2015}{2016}+\frac{2016}{2017}=1-\frac{1}{2016}+1-\frac{1}{2017}>1\)
\(B=\frac{2015+2016}{2016+2017}< \frac{2016+2017}{2016+2017}=1\)
Suy ra \(A>B\).